Calculation of free baryon spectral densities at finite temperature - Chrisanthi Praki (Proceedings of The 33rd International Symposium on Lattice Field Theory — PoS(LATTICE 2015), 2016)
Following a recent lattice study of nucleon parity doubling at finite temperature from the computation of the two-point nucleon correlators, we study the spectral functions of free nucleons atfinite temperature. Spectral densities in the continuum are presented along with a comparison to(free) results on the lattice. Particular attention is given to lattice artefacts at higher energies.